A review of surface roughness generation in ultra-precision machining. (April 2015) - Zhang, S.J.; To, S.; Wang, S.J.; Zhu, Z.W.
Abstract: Ultra-precision machining (UPM) is capable of manufacturing a high quality surface at a nanometric surface roughness. For such high quality surface in a UPM process, due to the machining complexity any variable would be possible to deteriorate surface quality, consequently receiving much attention and interest. The general factors are summarized as machine tool, cutting conditions, tool geometry, environmental conditions, material property, chip formation, tool wear, vibration etc. This paper aims to review the current state of the art in studying the surface roughness formation and the factors influencing surface roughness in UPM. Firstly, the surface roughness characteristics in UPM is introduced. Then in UPM, a wide variety of factors for surface roughness are then reviewed in detail and the mechanism of surface roughness formation is concluded thoroughly. Finally, the challenges and opportunities faced by industry and academia are discussed and several principle conclusions are drawn. Graphical abstract: Highlights: The surface roughness characteristics in UPM is elaborated. The factors and mechanism of surface roughness formation are reviewed in detail. The challenges and opportunities faced by industry and academia are discussed. The key issues are drawn to surface roughness formation in UPM.